EMPOWERMENT OF HUMAN RESOURCES, AS THE KEY OF ORGANIZATIONAL SUCCESS - Mukhtadi Mukhtadi (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The success of an organization besides being influenced by various factors is also strongly influenced by the quality of human resources, it is necessary to empower human resources according to the needs of the organization, through education and training, so that human resources are ready to carry out their duties and responsibilities. Human resources are the most important part of the organization, one of the keys to the success of the organization is the level of quality and expertise of human resources that are owned by the organization, dynamic organizations and want to succeed in global competition. Human. Keyword: Empowerment, Human Resources. Organizational Success